1992
DOI: 10.1037/0022-3514.62.6.1036
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization of positive and negative self-knowledge: Keeping bad apples out of the bunch.

Abstract: Three studies examined whether categorical organization of knowledge about the self explains variance in self-esteem and depression beyond that which is accounted for by sheer amount of positive or negative content. Compartmentalization is the tendency to organize positive and negative knowledge about the self into separate, uniformly valenced categories (self-aspects). As long as positive self-aspects are activated, access to negative information should be minimized. Compartmentalization was associated with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
441
3
5

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 322 publications
(470 citation statements)
references
References 49 publications
21
441
3
5
Order By: Relevance
“…In addition to the overall evaluation of one's worth, people also have stable attitudes reflecting their feelings of worth in each of the behavioral domains that comprise the self-concept (Harter, 1990). Studies have shown that people evaluate themselves differently in each behavioral domain that comprises the self-concept and that these domain-specific self-evaluations serve as the foundation that gives rise to one's overall level of self-satisfaction (Marsh, 1986;Pelham and Swann, 1989;Showers, 1992).…”
Section: The Total Self-conceptmentioning
confidence: 99%
“…In addition to the overall evaluation of one's worth, people also have stable attitudes reflecting their feelings of worth in each of the behavioral domains that comprise the self-concept (Harter, 1990). Studies have shown that people evaluate themselves differently in each behavioral domain that comprises the self-concept and that these domain-specific self-evaluations serve as the foundation that gives rise to one's overall level of self-satisfaction (Marsh, 1986;Pelham and Swann, 1989;Showers, 1992).…”
Section: The Total Self-conceptmentioning
confidence: 99%
“…A card sorting task measured the content and structure of beliefs about the parent. This task has been used to assess the structure of knowledge about the self (Showers, 1992;cf. Linville, 1987;Zajonc, 1960) and romantic partners (Showers & Kevlyn, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Because these different types of organization of selfknowledge are believed to affect the accessibility of positive and negative self-beliefs, evaluative organization may moderate the impact of specific beliefs on self-esteem and mood (Showers, 1992). Specifically, the basic model predicts that when positive self-aspects are important, compartmentalized structures (i.e., segregating positive and negative self-traits into separate self-aspect categories) will be associated with the most positive outcomes, such as lower depression and higher self-esteem.…”
Section: Self-structurementioning
confidence: 99%
See 2 more Smart Citations